Pengaruh Perbedaan Waktu Pemanasan terhadap Karakteristik Kadar Air, Kadar Abu, Daya Larut, dan Sifat Sensoris Serbuk Minuman Instan Kulit Buah Naga (Hylocereus Polyrhizus) Menggunakan Metode Konvensional - Dian Fitriarni; Maichael Effendi (Universitas 17 Agustus 1945 Semarang, 2024)
Development of products based on ingredients rich in nutrients and bioactive compounds needs to be developed. High sources of antioxidants can be found from various fruits and their waste. Dragon fruit peels is known to contain various antioxidant compounds that are useful for body health. Instant dragon fruit peels drink is an instant food product processed from dragon fruit waste. The instant drink processing technique in this study uses conventional methods.The purpose of this study was to determine the effect of heating time on the chemical quality of instant drink powder in terms of water content and ash content and organoleptic tests were also carried out to determine the effect of the process on the sensory characteristics of color, taste, and aroma. Based on the results obtained, the water content of instant dragon fruit peels powder ranged from 1.97-1.98%, KND 3 samples with a heating treatment of 30 minutes had the highest water content (1.98%). The ash content value of the product ranged from 0.17-0.83% where the KDN3 treatment (heating time 30 minutes) showed the highest ash content (0.83%). The results of the analysis of this study showed a solubility of 97.6-99.15%. The results of the organoleptic test (hedonic test) on the color attribute showed a significant difference (P>0.05) between the 10 and 20 minute heating treatments with the product from the heating results with a heating time of 30 minutes where the panelists liked the color and aroma of the product from the 10 and 20 minute heating time treatments.